Chemical and Physical Denudation Rates in the Poços de Caldas Alkaline Massif, Minas Gerais State, Brazil - Conceição, Fabiano Tomazini da [UNESP] (2024)
Chemical and physical denudation rates have been assessed in areas with different lithologies. Surprisingly, there are no studies that attempt to document these rates in the Poços de Caldas Alkaline Massif (PC), the largest alkaline magmatism in South America and an important Al supergene deposit in Brazil. Therefore, the chemical and physical denudation rates were assessed and explained in the PC. Surface water and rainwater samples were collected at the Amoras Stream basin, covering one complete hydrological cycle (2016). All samples were analyzed for dissolved cations, silica, anions, total dissolved solids (TDS), and total suspended solids (TSS). The results reflected the seasonal variation on discharge, water temperature, and electrical conductivity in the Amoras Stream, with most of the cations, anions, silica TDS, and TSS being carried in the wet season. Partial hydrolysis and silicate incongruent dissolution are the main water/rock interactions in the PC, with an atmospheric/soil CO2 consumption rate of 1.6 × 105 mol/km2/a. The annual fluxes of Cl−, PO43−, NO3−, and Al3+ were significantly influenced from rainwater. Chemical and physical weathering rates were 4 ± 0.8 and 3.0 ± 0.6 m/Ma in the PC, respectively, indicating that under the current climatic condition, the weathering profile is in dynamic equilibrium.